Thermoluminescence features of commercial glass and retrospective accident dosimetry - Yasmin, Sabina; Khandaker, Mayeen Uddin; Zahariman, Siti Rozaila; Rashid, Md Abdur; Bradley, D.A.; Sani, Siti Fairus Abdul (Elsevier, 2020)
Five window glass brands popularly used in Bangladeshi dwellings have been analyzed for retrospective accident dosimetry, being inexpensive, highly effective as a barrier to moisture and naturally transparent at optical wavelengths. In examining their potential for dosimetry, study has been made of the annealing – irradiation - readout steps contributing to characterization of the various key thermoluminescence properties. These include the respective glow curves, relative sensitivity, dose response, energy response, reproducibility and fading. An ERESCO model 200 MF4-RW X-ray machine and a Gammacell-220 60Co source was used for sample irradiation, while a Harshaw 3500 TLD reader (USA) supported by WinREMS software was used for TL readouts. Within the γ-radiation dose range up to 50 Gy, the various TL parameters show Nasir glass (a locally produced glass brand) to offer the most promising performance for retrospective dosimetry. Fading studies indicate the reconstruction of absorbed dose to be possible for periods of up to four weeks post-exposure. Energy dispersive X-ray analysis shows the Zeff of the various glass to be in the range 12.5–15.1, closely according with that of TLD-200, a commercial dosimeter used for low-level environmental radiation dosimetry. Present work constitutes the first such study of low-cost commercial glass for doses in the range 10–50 Gy, previous literature relating to doses from 50 Gy up to 20 kGy. © 2019 Elsevier Ltd